Thermophysical and electro-optical properties of carbon nanomaterials based nanofluids / Ali Mohammed Moqdad Ijam - Ali Mohammed, Moqdad Ijam (2017)
Nanofluids are simply the dispersion of nanometer-sized particles in different fluids. They are suitable candidates for heat transfer applications due to their high thermal conductivity. Poor stability is the main important disadvantage of the nanofluids in practical applications. The sedimentation of the nanoparticles is linked to the colloidal suspension properties. Antifreeze fluids such as glycerol (Gly), ethylene glycol (EG) and propylene glycol (PG) are used as a coolant due to their high boiling temperature and low freezing point compared to deionized water (DW). The aim of this research is to prepare a stable carbon nanomaterials- antifreeze/deionized water based nanofluids. Graphene oxide nanosheets (GONs) are prepared by using chemical treatment. Pristine-MWCNT is functionalized by using an acid mixture. In the present study, base fluids namely Gly/DW, EG/DW and PG/DW are used with different mixing ratios. The nanofluids are prepared by using two-step and hierarchical methods. The concentrations of GONs nanofluids are ranging from 0 to 0.10 wt.% and F-MWCNT/GONs nanofluids are in the range of 0 to 0.18 wt.%. The stabilities of the nanofluids are investigated with respect to sedimentation time by using UV-Visible technique. The effects of both concentration and temperature on the thermophysical properties (thermal conductivity, viscosity, density and specific heat) are investigated. Furthermore, the electro-optical properties of the nanofluids are examined as working fluid in the direct absorption solar collector. The forced convection heat-transfer of both base fluids and nanofluids are assessed. The experiments are carried out by using a smooth stainless steel tube and subjected to constant heat flux. The obtained results from the base fluid are evaluated with Shah’s equation in laminar flow conditions. In general, the prepared nanofluids exhibit a good stability in long and short term. Thermal and electrical conductivities of nanofluids are enlarged with increasing temperature and loading. At a loading of 0.10 wt.%, the thermal conductivity of the GONs-Gly/DW and GONs-EG/DW is improved by 11.7% and 10.47%, respectively. Nanofluids are simply the dispersion of nanometer-sized particles in different fluids. They are suitable candidates for heat transfer applications due to their high thermal conductivity. Poor stability is the main important disadvantage of the nanofluids in practical applications. The sedimentation of the nanoparticles is linked to the colloidal suspension properties. Antifreeze fluids such as glycerol (Gly), ethylene glycol (EG) and propylene glycol (PG) are used as a coolant due to their high boiling temperature and low freezing point compared to deionized water (DW). The aim of this research is to prepare a stable carbon nanomaterials- antifreeze/deionized water based nanofluids. Graphene oxide nanosheets (GONs) are prepared by using chemical treatment. Pristine-MWCNT is functionalized by using an acid mixture. In the present study, base fluids namely Gly/DW, EG/DW and PG/DW are used with different mixing ratios. The nanofluids are prepared by using two-step and hierarchical methods. The concentrations of GONs nanofluids are ranging from 0 to 0.10 wt.% and F-MWCNT/GONs nanofluids are in the range of 0 to 0.18 wt.%. The stabilities of the nanofluids are investigated with respect to sedimentation time by using UV-Visible technique. The effects of both concentration and temperature on the thermophysical properties (thermal conductivity, viscosity, density and specific heat) are investigated. Furthermore, the electro-optical properties of the nanofluids are examined as working fluid in the direct absorption solar collector. The forced convection heat-transfer of both base fluids and nanofluids are assessed. The experiments are carried out by using a smooth stainless steel tube and subjected to constant heat flux. The obtained results from the base fluid are evaluated with Shah’s equation in laminar flow conditions. In general, the prepared nanofluids exhibit a good stability in long and short term. Thermal and electrical conductivities of nanofluids are enlarged with increasing temperature and loading. At a loading of 0.10 wt.%, the thermal conductivity of the GONs-Gly/DW and GONs-EG/DW is improved by 11.7% and 10.47%, respectively.